Ecologia de estradas em regiões neotropicais: revisão - Rizatti, Leonardo Guerra [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
The human development requires that urban and industrial centers to be interconnected, with different modes of transport, among which the land transport is the most important. The roads may cross sections of remnant forests, which contain considerable diversity of species. Besides habitat fragmentation, the roads can also hinder connectivity between different patches. This kind of impact is not very well known. We reviewed the literature on Road Ecology in the Neotropics, and its relation to conservation of the biodiversity. We considered 32 papers on this issue. We compiled what is known and what the direction to take, as well as failures to be avoid in the samples, for future studies involving Road Ecology. Despite the growing trend of this subject, flaws in the methods for this type of studies show that there is no standardization of sampling effort or of experimental design for these studies. We also found that there is a lack of study of some taxonomic classes. The simple animal roadkills records do not make clear the impacts of the roads. The necessity of different designs for specific taxonomic classes must be considered, in order to produce better quality data and reliable results. Animals can avoid roads, getting isolated and limited to smaller areas of life. The dispersal and colonization of exotic flora species are facilitated by roads. Nevertheless, it is not known how or at which scale, these invasions impact the local communities. Finally, we proposed a flowchart as a conceptual model illustrating the potential impacts of roads on biodiversity and ecology interactions

O desenvolvimento humano obriga que diversos centros urbanos e industriais estejam ligados com os mais diferentes meios de transporte, dos quais o terrestre consiste em um dos mais importantes. Estradas podem cruzar trechos de remanescentes de matas, que comportam considerável diversidade de espécies. Além de dividir esses remanescentes, podem ainda dificultar a conectividade entre diferentes fragmentos. Sabe-se muito pouco sobre esse tipo de impacto. Realizamos uma revisão de literatura sobre o que foi produzido nos Neotrópicos sobre o tema Ecologia de Estradas e sua relação com conservação da biodiversidade. Reunimos 32 trabalhos que abordaram o tema. Unificamos o que se sabe e quais as direções a serem tomadas, bem como as falhas a evitar nas amostragens, para os próximos estudos envolvendo Ecologia de Estradas. Apesar da tendência crescente do assunto, falhas encontradas nos métodos científicos para esse tipo de estudos mostram que não há padronização nos esforços de amostragem ou em desenhos experimentais nesses estudos, e que algumas classes taxonômicas são pouco estudadas. O simples registro de atropelamento animais não deixa claro o impacto decorrente das estradas. A necessidade de diferentes delineamentos para classes taxonômicas específicas deve ser observada para a produção de melhores resultados e dados confiáveis. Animais podem evitam as estradas, ficando isolados e limitados a menores áreas de vida. A dispersão e instalação de espécies exóticas de flora é facilitada por estradas, mas ainda não se sabe como, ou qual a magnitude desse impacto nas comunidades locais. Propusemos um fluxograma como modelo conceitual ilustrando os impactos potenciais das estradas em relação à biodiversidade e suas interações ecológicas
Keywords: Ecologia; Estradas; Acidentes de trânsito; Ecologia da paisagem; Biodiversidade